ANALISIS FAKTOR YANG MEMPENGARUHI PELAYANAN PENGAJUAN IZIN OPERASIONAL KETENAGAKERJAAN ( SIO) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU PROVINSI KALIMANTAN TIMUR - Norma Yunita (ADMINISTRASI PUBLIK, 2018)
NORMA YUNITA, 2018, NPM. 14.11.1001.3509.145 research title “Analysis of Factors Affecting the Operational Service of Employment Operational Permits (Sio) in the One Stop Investment Services and One Stop Services in East Kalimantan Province”.Lecture : Bapak Drs. H. Maskan, AF, M.Si dan Bapak Drs. Jamil Bazarah, M.Si.This study aims to find out (1) how the general description of licensing services at the Capital Investment and Service Terpadusatu Pintu (2) factors that affect the quality of service at the Department of Investment and Integrated Services one door East Kalimantan Province.This research method is qualitative research. Qualitative research is an approach that is also called investigative approach because usually researchers collect data by face to face face-to-face and interact with people in place of research. Data collection was done by interviewing technique and participant observation. Data analysis in this research use three paths that is data reduction, data presentation, and conclusion.The results of this study indicate that (1) Quality of service at the Investment Service and Terpadusatu Pintu service already reflects the 14 service standards according to the index of community satisfaction in accordance with regulations KEP/25/M.PAN/2/2004 about Utilization of State Apparatus. (2) Factors affecting the quality of service at the Investment Department and Integrated Services one Door, among others, is the lack of quality of human resources, and kuantias employee licensing services.